Contribution of Lordotic Correction on C5 Palsy Following Cervical Laminectomy and Fusion. Issue 6 (20th January 2016) - Cherian, Jacob; Mayer, Rory R.; Haroun, Kareem B.; Winnegan, Lona R.; Omeis, Ibrahim
Abstract: BACKGROUND: C5 palsy is a well-reported complication of cervical spine surgery. The implication of sagittal cervical alignment parameters and their changes after surgery on the incidence of C5 palsy remains unclear. OBJECTIVE: We review cervical alignment changes in our cases of C5 palsy after cervical laminectomy and fusion. METHODS: Cases of C5 palsy were retrospectively compared with a control group. Preoperative and postoperative upright plain film radiographs were analyzed in blinded fashion. RESULTS: Spine registry analysis identified 148 patients who underwent cervical laminectomy and fusion by the senior author over 5 years. There were 18 (12%) cases complicated by postoperative C5 palsy. Nine of these 18 patients had prerequisite upright films and were compared with a randomly constructed case control group of 20 patients. There were no statistically significant differences between the 2 groups in age, proportion of males, and preoperative Nurick score. Measures of sagittal alignment did not differ significantly between the 2 groups on preoperative and postoperative imaging. When comparing the amount of alignment change between preoperative and postoperative upright imaging, however, patients with C5 palsy had a statistically higher amount of average C4-C5 Cobb angle change (−2.53 vs 0.78°; P = .01). Logistic regression analysis demonstrated that lordotic change in both C4-C5 and C2-C7 Cobb angles were associated with development of palsy. CONCLUSION: Lordotic cervical correction, as measured on upright imaging, was statistically larger in patients who had C5 palsy. The role of deformity correction in C5 palsy deserves further study and may inform intraoperative decision making.